2015
DOI: 10.1682/jrrd.2014.11.0289
|View full text |Cite
|
Sign up to set email alerts
|

Mixed methods study examining work reintegration experiences from perspectives of Veterans with mental health disorders

Abstract: Abstract-Recent findings have demonstrated that reintegration for Veterans is often challenging. One difficult aspect of reintegration-transitioning into the civilian workplace-has not been fully explored in the literature. To address this gap and examine work reintegration, this mixed methods study examined the perspectives of Veterans with mental health disorders receiving Department of Veterans Affairs healthcare. Forty Veterans rated factors that affect work success; participants also provided narratives o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
44
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 30 publications
6
44
0
Order By: Relevance
“…Furthermore, recent studies examining both patient and provider perspectives have identified low work-related confidence and low motivation as major barriers to successful work outcomes among persons with mental illness receiving SE services (Corbière et al, 2011;Kukla, et al, 2015a;. In addition, the ways in which persons with mental health disorders think about themselves and work has been qualitatively linked with community work success (Kukla et al, 2015b;Williams et al, 2016). Lastly, across qualitative studies examining employed persons with mental illness, job tenure has been associated with one's perception of competence and efficacy related to the job (Williams et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, recent studies examining both patient and provider perspectives have identified low work-related confidence and low motivation as major barriers to successful work outcomes among persons with mental illness receiving SE services (Corbière et al, 2011;Kukla, et al, 2015a;. In addition, the ways in which persons with mental health disorders think about themselves and work has been qualitatively linked with community work success (Kukla et al, 2015b;Williams et al, 2016). Lastly, across qualitative studies examining employed persons with mental illness, job tenure has been associated with one's perception of competence and efficacy related to the job (Williams et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…), as they reintegrate into the civilian world after extended periods of combat deployments and active duty military involvement (13). Taken together, these circumstances suggest the need to further consider influences that may be distinctly salient to Veteran work success.…”
Section: Introductionmentioning
confidence: 99%
“…They are not only leaving the military as a job, but also as a way of life. This can also lead to a higher rate of mental health disorders [13,19], as there is a mismatch between veterans' expectations and reality. Many veterans will feel they are returning to a "normal" way of life, but in reality, due to the nature of military service and the emotional and physical scars veterans endure during their deployment, they can often feel isolated or alienated upon return to civilian life [20].…”
Section: What Are the Challenges Associated With Transition From Milimentioning
confidence: 99%
“…Disabilities and other factors contribute to difficulties in accessing jobs, including employer stereotyping of ex-defence personnel [12], and in turn being unable to secure employment contributes to their stress. In this context, it is important that the relationship between military service and post-service access to suitable employment is evaluated, as the concerns facing ex-defence personnel are complex, and impact a multitude of different areas in civilian life (health care, employment, disability), and therefore they require more specialist case-management services [13].…”
Section: Introductionmentioning
confidence: 99%